HISTOPATHOLOGICAL STRUCTURE OF THE RAT KIDNEY AFTER ADMINISTRATION OF SAPPAN WOOD EXTRACT (Caesalpinia sappan L.) IN IRON OVERLOAD CONDITION - Jeri Nobia Purnama; Firdawati, Nurul; Khristian, Erick; Safitri, Ratu; Utama, Gemilang Lara; Fakhira, Anisa Muthia (Universitas Airlangga, 2024)
Excessive amounts of iron in the body can lead to damage to various organs, including the kidneys. Iron chelators have been demonstrated to effectively reduce the accumulation of this excess iron. This study aims to investigate the impact of administering sappan wood extract (Caesalpinia sappan) as an adjuvant to iron chelators on the structure and function of kidneys in a rat model of iron overload. The experimental research, spanning 28 days, employed a Completely Randomized Design (CRD) involving 30 male Wistar rats (Rattus norvegicus) distributed across 6 test groups. Iron dextran at 60 mg/kg bb induced iron overload, while a comparative iron chelator, deferiprone, was given at 1.35 mg/kg bb. Various doses of Sappan wood extract (SWE) 100, 150, and 200 mg/kg bb were administered to separate test groups. The parameters that are being observed include the distribution of iron and the structure of kidney injury. At a 95% confidence level, the acquired data were examined using analysis of variance (ANOVA), and the Duncan test was used to see whether there were any differences. The study's findings demonstrated that each treatment group's kidney iron levels differed from the excess iron-containing control group (p <0.05). The histological investigation results demonstrated a significant difference in damage scores (p <0.05) between the groups administered secang wood extract and the excess besei control group. Adminstered of 100 mg/kgbw dose of EKS might lower their organ iron levels and lessen the harm that the iron did to their kidneys. Keyword: Sappan Wood (Caesalpinia sappan L.), Iron Overload, Kidney